A Comparison of the Rise of the Temperature of an Unprotected Steel Column Subjected to the Standard Fire Curve ISO 834 and to a Natural Fire Model in the Office - SZUMIGAŁA, Maciej; POLUS, Łukasz (Engineering Transactions, 2015)
This paper presents a comparison of the changes in the temperature of a steel HEB 300 section column in a standard fire curve and in a natural fire. The EN 1991-1-2 standard and the fire dynamics simulator (FDS) were used to calculate the temperature of the steel column in a fire situation. The temperature of the steel column based on Eurocodes using the ISO 834 curve was different from the temperature obtained from the fire dynamics simulator, modeling a natural fire.